2018
DOI: 10.7150/jca.21336
|View full text |Cite
|
Sign up to set email alerts
|

Early and Partial Reduction in CD4+Foxp3+ Regulatory T Cells during Colitis-Associated Colon Cancer Induces CD4+ and CD8+ T Cell Activation Inhibiting Tumorigenesis

Abstract: Colorectal cancer (CRC) is the second most commonly diagnosed cancer in women and the third in men in North America and Europe. CRC is associated with inflammatory responses in which intestinal pathology is caused by different cell populations including a T cell dysregulation that concludes in an imbalance between activated T (Tact) and regulatory T (Treg) cells. Treg cells are CD4+Foxp3+ cells that actively suppress pathological and physiological immune responses, contributing to the maintenance of immune hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 56 publications
(70 reference statements)
1
26
0
Order By: Relevance
“…The role and potential mechanism of CD4 + FOXP3 + Tregs have also been investigated in colitis-associated colon and colorectal cancer. Notably, Olguín et al (29) discovered that the percentage of CD4 + FOXP3 + Tregs was increased in colitis-associated colon cancer. Another study by Syed Khaja et al (17) revealed that numbers of CD4 + FOXP3 + Tregs were increased in colorectal cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“…The role and potential mechanism of CD4 + FOXP3 + Tregs have also been investigated in colitis-associated colon and colorectal cancer. Notably, Olguín et al (29) discovered that the percentage of CD4 + FOXP3 + Tregs was increased in colitis-associated colon cancer. Another study by Syed Khaja et al (17) revealed that numbers of CD4 + FOXP3 + Tregs were increased in colorectal cancer tissues.…”
Section: Discussionmentioning
confidence: 99%
“… 5 Tregs and Th17 cells have tumor-promoting functions during CAC formation, 6 , 7 whereas CD8 + T cells protect against CAC tumorigenesis. 8 In addition, cancer-associated fibroblasts (CAFs) promote the growth of colitis-associated neoplasms through activation of ERK signaling and increase colon cancer angiogenesis via IL-6 and VEGF signaling. 9 , 10 In addition to providing a survival advantage by inducing angiogenesis, tumor-associated vessels contribute to CAC tumorigenesis by facilitating pro-inflammatory leukocyte extravasation.…”
Section: Introductionmentioning
confidence: 99%
“…The multiple subpopulations of Tregs are distinguished by the expression of different cell surface markers, including FoxP3, CD4, CD25 and CD127 ( 45 , 46 ). The present study examined the level of CD4 + Foxp3 + Tregs, which has been widely reported in previous studies ( 47 52 ). The multiple subpopulations of Tregs may play different roles in oral carcinogenesis and the authors hope to examine CD4 + CD25 + CD127 low FoxP3 + Tregs in future studies.…”
Section: Discussionmentioning
confidence: 91%